Walkable Urban Design Attributes and Japanese Older Adults’ Body Mass Index: Mediation Effects of Physical Activity and Sedentary Behavior - Koohsari, Mohammad Javad (Am J Health Promot, 2018)
PURPOSE: The purposes of this study were to examine associations between objectively measured walkable urban design attributes with Japanese older adults’ body mass index (BMI) and to test whether objectively assessed physical activity and sedentary behavior mediated such associations. DESIGN: Cross-sectional. SETTING: Matsudo City, Chiba Prefecture, Japan. PARTICIPANTS: Participants were 297 older residents (aged 65-84 years) randomly selected from the registry of residential addresses. MEASURES: Walkable urban design attributes, including population density, availability of physical activity facilities, intersection density, and access to public transportation stations, were calculated using geographic information systems. Physical activity, sedentary behavior, and BMI were measured objectively. ANALYSIS: The relationships of walkable urban design attributes, Walk Score®, and BMI were examined by multiple linear regression with adjustment for covariates in all models. Mediation effects of the physical activity and sedentary behavior variables in these relationships were tested using a product-of-coefficients test. RESULTS: Higher population density and Walk Score® were associated with lower BMI. Light and moderate-to-vigorous physical activities partially mediated the relationships between these walkable urban design attributes and BMI. CONCLUSIONS: Developing active-friendly environmental policies to (re)design neighborhoods may not only promote active transport behaviors but also help in improving residents’ health status in non-Western contexts.